2020
DOI: 10.2174/1573407215666190409105351
|View full text |Cite
|
Sign up to set email alerts
|

Bioinorganic Chemistry of Platinum(IV) Complexes as Platforms for Anticancer Agents

Abstract: The current review focuses on the comprehensive studies of platinum-based complexes that are known to exhibit anticancer properties. The capacity to perceive, to comprehend at the sub-atomic level, and to treat sicknesses has brought sufficient metal-particle work which constitutes an imperative part of therapeutic bioinorganic science. Understanding the biochemistry and sub-atomic science of detoxification mechanism of metals can help in advancing as well as enhancing the anticancer property of metal complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Four octahedral Pt(IV) compounds have entered clinical trials ( tetraplatin , iproplatin , satraplatin , and LA-12 , Figure 9 ). Unfortunately, LA-12 failed in phase I trials, while tetraplatin showed high neurotoxicity and was not investigated after phase I. Iproplatin showed limited benefits in phase II trials, and studies on the orally available satraplatin were dropped in phase III ( Nagyal et al, 2020 ; Chunyan et al, 2021 ).…”
Section: Redox Enzymes As a Target Of Drugs For Cancer Treatmentmentioning
confidence: 99%
“…Four octahedral Pt(IV) compounds have entered clinical trials ( tetraplatin , iproplatin , satraplatin , and LA-12 , Figure 9 ). Unfortunately, LA-12 failed in phase I trials, while tetraplatin showed high neurotoxicity and was not investigated after phase I. Iproplatin showed limited benefits in phase II trials, and studies on the orally available satraplatin were dropped in phase III ( Nagyal et al, 2020 ; Chunyan et al, 2021 ).…”
Section: Redox Enzymes As a Target Of Drugs For Cancer Treatmentmentioning
confidence: 99%
“…The diazido Pt(IV) The photoreductive Pt(IV) complexes with azide ligands perfectly incorporate the photodecomposition of Pt(IV) complex with the light sensitivity of azido complexes, making itself the potential PACT (photoactivated anticancer chemotherapy) prodrugs. Since the first report of such a complex with a structure of trans-[Pt(N 3 ) 2 (CN) 4 ] 2− by Vogler et al in 1978, prominent progress has been achieved in the development of complexes of new structures, understanding the mechanisms of the activation and phototoxicties in medicinal application [73][74][75][76][77].…”
Section: Diazido Platinum(iv) Complexes For Photoactivated Anticancer...mentioning
confidence: 99%